Non-pharmacological intervention in the treatment of insomnia - the efficacy of weighted blankets - Monika Sroczyńska; Anna Luchowska; Aleksandra Żaczek (Kazimierz Wielki University, 2023)
Introduction Insomnia is a common sleep disorder characterized by difficulty falling asleep, staying asleep, or getting restful sleep. Research suggests that 30-50% of adults experience sleep problems. Chronic lack of sleep has been linked to a range of negative health outcomes, including obesity, hypertension, diabetes, stroke, coronary heart disease and increased mortality. One promising non-pharmacological treatment for sleep issues is the use of weighted blankets. Weighted blankets provide deep pressure stimulation that can relax the body and promote sleep, making them a useful tool for people with insomnia.   Aim of the study The purpose of this study was to investigate the effectiveness of weighted blankets as a non-pharmacologic intervention for treating insomnia.   Materials and methods A search was conducted using PubMed and Google Scholar databases. Articles were searched in English using the following key words: weighted blankets; insomnia; sleep.   Results Weighted blankets resulted in significant improvements in Insomnia Severity Scale scores. The blankets made it easier to fall asleep, improved sleep quality and provided a higher level of rest in the morning. They also reduced stress levels while falling asleep and increased feelings of relaxation. There was an increase in daytime activity levels and a reduction in daytime fatigue symptoms observed. The use of weighted blankets improved daytime functioning and reduced the consumption of sleep medications in people with psychiatric comorbidities who suffered from insomnia. No negative effects on vital signs or serious side effects were found.   Conclusions Findings indicate that weighted blankets are an effective, safe and clinically meaningful treatment for insomnia.